2019
DOI: 10.1515/jbcpp-2019-0266
|View full text |Cite
|
Sign up to set email alerts
|

Antiaggregation effect of clopidogrel in coronary heart disease patients using omeprazole

Abstract: BackgroundAntiplatelet agents used in coronary heart disease (CHD) cause gastrointestinal side effects. Omeprazole can prevent and cure these antiplatelet side effects. Clopidogrel combined with aspirin increases the risk of gastrointestinal tract ulcers and bleeding. This research studied the effect of omeprazole on the antiplatelet effect of clopidogrel.MethodsCHD patients using clopidogrel and aspirin receive omeprazole 20 mg in a single dose for 10 days. Platelet antiaggregation point for clopidogrel was m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…In the RCT study, patients were stratified by platelet aggregation inhibition rates, and no significance was found between the highest and lowest groups, which represent patients with a high risk of bleeding or thrombosis due to the efficacy of clopidogrel. Data from several observational studies 52,55,59,60 indicated no significant differences between the platelet aggregation function in patients treated with omeprazole and a control group. The treatment duration ranged from 2 days to 2 years in these studies.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the RCT study, patients were stratified by platelet aggregation inhibition rates, and no significance was found between the highest and lowest groups, which represent patients with a high risk of bleeding or thrombosis due to the efficacy of clopidogrel. Data from several observational studies 52,55,59,60 indicated no significant differences between the platelet aggregation function in patients treated with omeprazole and a control group. The treatment duration ranged from 2 days to 2 years in these studies.…”
Section: Resultsmentioning
confidence: 99%
“…9–12,16–51 The qualitative assessment of the platelet function test included 18 studies. 11,17,23,24,37,50,52–63 The PRISMA flow diagram (Fig. 1) shows the complete screening process, including the reasons for exclusion.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation